PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEADILAN ORGANISASI TERHADAP KOMITMEN ORGANISASI KARYAWAN DIBAGIAN HOUSEKEEPING PADA HOTEL BALI DYNASTY RESORT KUTA - Oceani, Ni Made Puspita; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen; Vol 4 No 10 (2015), 2015)
The concept of organizational commitment is based on the assumption that the commitment of the organization to have a relationship, not just the employee and the organization, but in the surrounding communities. The purpose of this study was to determine the effect of transformational leadership style and organizational justice on organizational commitment. The study was conducted at the Hotel Bali Dynasty Resort Kuta. The number of samples taken 80 employees housekeeping section, the census method or saturated samples. A multiple linear regression analysis techniques are used. Variables with standardized beta coefficients greater is justice organization that is equal to 0.547. Justice organizations greater influence on organizational commitment. This is because of the concern shown on the organization's employees, both in the system of remuneration or working procedures, the employee will increase the loyalty and commitment to the company.
Keywords: transformational leadership style, organizational justice, organizational commitment